Intestinal parasites infecting captive non-human primates in Italy - Rondón, Silvia; Cavallero, Serena; Montalbano Di Filippo, Margherita; De Liberato, Claudio; Berrilli, Federica; Capitani, Nazareno; D’Amelio, Stefano (Frontiers in Veterinary Science, 2024)
Non-human primates (NHPs) living in captive conditions are susceptible to intestinal parasites that can contribute to mortality and morbidity, and cause zoonotic infections. Thus, parasite surveys on NHP populations under human care are relevant as part of the evaluation of NHPs welfare and in the zoonotic disease risk assessment, as well as in the exploration of parasite transmission pathways, according to the One-Health concept. This study aimed to identify intestinal parasites infecting NHPs living in two wildlife recovery centers and in a zoological garden, in Italy. Ninety-three fecal samples from Macaca tonkeana, Macaca fascicularis, Sapajus apella, Chlorocebus aethiops, Macaca fuscata, Macaca sylvanus and Cebus capucinus were collected at Piano dell'Abatino Park (Lazio), and fecal smears and flotation were performed in order to identify parasites according to morphological keys. Additionally, one carcass of M. fuscata from the Bioparco Zoological Garden of Rome (Lazio) and one of M. fascicularis from the Center for the Recovery of Exotic and Maremma Wild Animals (Tuscany) were necropsied and intestinal adult nematodes were collected and characterized at morphological and molecular level, using the mitochondrial cox1 and rrnL markers. Protozoans (Entamoeba coli, Iodamoeba bütschlii, Dientamoeba fragilis-like, Giardia duodenalissp.), chromists (Balantidium/Buxtonella sp.) and nematodes (Capillaria sp., Trichuris sp., strongyliform larvae and Oesophagostomum sp.) were found through fecal smears and flotation. The collected adult nematodes from dead NHPs were morphologically identified as whipworms (genus Trichuris). Phylogenetic analyses grouped Trichuris specimens into the Trichuris trichiura complex of species, with specimens from M. fuscata clustering into a host-specific branch, and whipworms from M. fascicularis clustering within a clade formed by Trichuris infecting several primate species, including humans. The results here collected revealed the presence of potentially zoonotic parasites circulating in captive primates in Italy, providing useful information for the formulation of management and care plans for captive NHPs, and for the elaboration of safety measures for visitors and animal keepers.